Enterprise Risk Management Models - Olson, David L.; Wu, Desheng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Enterprise risk management has always been important. However, the events of the 21st Century have made it even more critical. The top level of business management became suspect after scandals at ENRON, WorldCom, and other business entities. Financially, many firms experienced difficulties from bubbles. The problems of interacting cultures demonstrated risk from terrorism as well, with numerous terrorist attacks, to include 9/11 in the U.S. Risks can arise in many facets of business. Businesses in fact exist to cope with risk in their area of specialization. Financial risk management has focused on banking, accounting, and finance. We have discussed several aspects of risk, to include information systems, disaster management, and supply chain perspectives. The bulk of this book is devoted to presenting a number of operations research models that have been (or could be) applied to enterprise supply risk management, especially from the supply chain perspective.
Enterprise Risk Management in Supply Chains -- Enterprise Risk Management Process -- Information Systems Security Risk -- Enterprise Risk Management in Projects -- Natural Disaster Risk Management -- Disaster Risk Management in China -- Value-Focused Supply Chain Risk Analysis -- Examples of Supply Chain Decisions Trading Off Criteria -- Simulation of Supply Chain Risk -- Value at Risk -- Chance Constrained Programming -- Data Envelopment Analysis in Enterprise Risk Management -- Portfolio Selection Under Fuzzy and Stochastic Uncertainty -- Business Scorecard Analysis to Measure Enterprise Risk Performance.
Keywords: Economics; Operations research; Economics/Management Science; Finance/Investment/Banking.; Operation Research/Decision Theory; Production/Logistics/Supply Chain Management